THE EFFECT OF REGIONAL LEVIES ON CAPITAL EXPENDITURE ALLOCATION IN REGENCIES/ CITIES OF CENTRAL JAVA - Amelia, Rizky Windar; Nugrahani, Cahaya (KIAT BISNIS, 2016)
This research aims to examine the effect of regional levies on capital expenditure allocation in regencies/ cities of Central Java. Regional levies are measured through the real regional fees in local government. Capital expenditure allocation is measured by using comparison percentage of capital expenditure budget and the total of regional expenditure budget. The sample used in this study were all regencies and cities in Central Java, amounting to 27 regencies and 6 cities. In selecting the samples, the researcher used total sampling technique, in which the entire population wassampled. Research testingwas conducted by using simple regression analysis. The research result on t test shows that regional levies do not have effect on capital expenditure allocation. It tells that the role of regional levies in the government and development budgeting in regencies/ cities of Central Javawas still very minimal